Continuous Training, Job Satisfaction, and Turnover Intention: Toward a Sustainable Workforce in Indonesia's Smelter - Irfan, Muh; Parwoto, Parwoto (International Journal of Human Behavior Management, 2026)
Purpose – This study examines the effect of continuous training on turnover intention through the mediating role of job satisfaction among employees of one of the mineral processing (smelter) companies in Morowali, Indonesia, based on the Job Demands–Resources (JD-R) theory. Methodology/approach – A quantitative explanatory study with a cross-sectional design was conducted involving 155 permanent employees selected through purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings – Continuous training has a significant negative effect on turnover intention and a significant positive effect on job satisfaction. Job satisfaction also has a significant negative effect on turnover intention and partially mediates the relationship between continuous training and turnover intention. These findings indicate that continuous training can serve as an effective employee retention strategy by enhancing job satisfaction and reducing employees' intention to leave. However, the findings should be interpreted considering the cross-sectional design and data collected from a single organization. Novelty/value – This study extends the application of the Job Demands–Resources (JD-R) theory within the context of Indonesia's smelter industry by demonstrating the mediating role of job satisfaction in explaining how continuous training contributes to employee retention. The findings provide practical implications for organizations seeking to build a sustainable workforce through continuous employee development. Keywords: Continuous Training; Job Satisfaction; Turnover Intention; Employee Retention; PLS-SEM